1976
DOI: 10.1007/bf01249442
|View full text |Cite
|
Sign up to set email alerts
|

Study of deterioration in long-term treatment of parkinsonism with L-Dopa plus decarboxylase inhibitor

Abstract: 35 parkinsonian patients have been treated over 3 years with L-Dopa combined with benserazide. After an impressive improvement during the first months of treatment a slow but significant deterioration of the patient's condition was observed. At the end of the observation period however their condition was still significantly better than before starting the treatment. A reduced mean L-Dopa dosage was ruled out as the cause of this deterioration. Withdrawal of the L-Dopa therapy for a few days in 13 patients pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

1977
1977
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(5 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“…They were 54 men and 68 women, aged 39 to 78 years (mean ± S.E., 59. 3 stage IV/V in 49. The interval between the first onset of disease and the initiation of L-dopa therapy was 24.58 ± 27.82 months in stage I/II patients, 48.6 ± 33.90 months in stage III patients, 82.39 ± 69.65 months in stage IV/V patients.…”
Section: Methodsmentioning
confidence: 99%
“…They were 54 men and 68 women, aged 39 to 78 years (mean ± S.E., 59. 3 stage IV/V in 49. The interval between the first onset of disease and the initiation of L-dopa therapy was 24.58 ± 27.82 months in stage I/II patients, 48.6 ± 33.90 months in stage III patients, 82.39 ± 69.65 months in stage IV/V patients.…”
Section: Methodsmentioning
confidence: 99%
“…Loss of Efficacy: While it is generally appreciated that Parkinson's disease progresses with time and that this factor accounts for at least some of the loss of effectiveness of levodopa, another factor to be considered is that prolonged treatment with levodopa could also be responsible, in part, for this unfavorable development. A number of studies demonstrated that the degree of benefit from levodopa therapy lessens with time (Hunteretal., 1973;Ludin and Bass-Verrey, 1976;Yahr, 1976; McDowell and Sweet (1976). Reproduced by permission of the publisher.…”
Section: Evidence Against Early Treatmentmentioning
confidence: 99%
“…4,5 Although the initial interest in surgery, based on promising results, had decreased because of new pharmacological alternatives, it was reconsidered in patients with low tolerance to medication during long-term therapy due to motor and non-motor side effects. 6,7 At the same time, a renewed interest in PD surgery came about because of technical improvements in imaging and a broadened knowledge of the physiology and biochemistry of the basal ganglia.…”
Section: Introductionmentioning
confidence: 98%